2020
DOI: 10.2196/18476
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Electronic Health Literacy Lens: Systematic Review of Electronic Health Interventions Targeted at Socially Disadvantaged Groups

Abstract: Background Electronic health (eHealth) has the potential to improve health outcomes. However, eHealth systems need to match the eHealth literacy needs of users to be equitably adopted. Socially disadvantaged groups have lower access and skills to use technologies and are at risk of being digitally marginalized, leading to the potential widening of health disparities. Objective This systematic review aims to explore the role of eHealth literacy and user … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(118 citation statements)
references
References 96 publications
3
115
0
Order By: Relevance
“…Yet, in a recent systematic review of eHealth interventions targeted at socially disadvantaged groups who are most at risk of low eHealth literacy, it was found that user-centered principles were not discussed, and eHealth literacy needs were generally not considered. User involvements were usually in the form of focus groups for needs assessment which involved limited respondents or at usability testing when the intervention was already designed (29). The findings reflect the growing concern that there is a lack of frameworks or guidelines to inform the development of digital health solutions that meet eHealth literacy needs (30), and disadvantaged populations are overlooked in digital health solution design (31).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Yet, in a recent systematic review of eHealth interventions targeted at socially disadvantaged groups who are most at risk of low eHealth literacy, it was found that user-centered principles were not discussed, and eHealth literacy needs were generally not considered. User involvements were usually in the form of focus groups for needs assessment which involved limited respondents or at usability testing when the intervention was already designed (29). The findings reflect the growing concern that there is a lack of frameworks or guidelines to inform the development of digital health solutions that meet eHealth literacy needs (30), and disadvantaged populations are overlooked in digital health solution design (31).…”
Section: Introductionmentioning
confidence: 90%
“…The findings reflect the growing concern that there is a lack of frameworks or guidelines to inform the development of digital health solutions that meet eHealth literacy needs (30), and disadvantaged populations are overlooked in digital health solution design (31). As such, vulnerable groups are at risk of becoming marginalized in the digital age (29,32).…”
Section: Introductionmentioning
confidence: 99%
“…Data from Pew Research Center have shown that internet use for racial and ethnic minorities is comparable to non-Hispanic whites [ 2 ]. As a result, health dissemination has become more streamlined, and use of the internet has become a popular tool for fostering complex conversations, increasing access to health information, and improving medical outcomes [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. For example, systematic reviews of digital health interventions have found clinical benefits among individuals with musculoskeletal conditions and improved quality of life and mental health outcomes for cancer patients [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results were consistent with those of previous studies worldwide (Hoogland et al 2020;Shiferaw et al 2020;Villadsen et al 2020). These identified non-modifiable factors can be used to determine which individuals are at risk of poor e-health literacy, and to indentify the vulnerable population that medical staff need to target (Cheng et al 2020). Nokes and Reyes (2019) implemented health education interventions for low-income elderly people (vulnerable population) in America, and the results showed that these interventions improved the elderly's e-health literacy and chronic disease self-management.…”
Section: Discussionmentioning
confidence: 99%